Couples' Remote Work Arrangements and Labor Supply - Sabrina Wulff Pabilonia; Victoria Vernon (Institute of Labor Economics (IZA), 2024)
Using the panel component of the Current Population Survey and questions on work-from-home intensity, the authors examine the relationships between partners' work location arrangements, weekly hours worked, and within-couple labor hours inequality. Fixed-effects estimates suggest a strong positive relationship between partners' decisions to work from home. On average, remote workers work fewer hours than onsite workers, while hybrid workers work more. Both partners switching from onsite to hybrid work is associated with a 5.4% increase in couple-level hours, while both switching to fully remote work is associated with a 3.2% decrease in couple-level hours. When women switch to hybrid work while their partners switch to remote, within-couple labor hours inequality decreases; women switching to remote work increases inequality. Results suggest that hybrid, but not remote, work could improve women's position in the labor market.
Keywords: J20; J22; J31; 330; working from home; telework; hybrid; remote; hours; gender inequality